John Walker - new paintings - Watkins, Jonathan 1957-; Watkins, Jonathan 1957- (Ikon Gallery, 2020)
Celebrating a major exhibition of new paintings by Birmingham-born artist John Walker (b. 1939), who studied at the Moseley School of Art, and later the Birmingham College of Art. He was the first artist to show at Ikon Gallery when it moved in 1972 to new premises in the Birmingham Shopping Centre above New Street Station. Here he presented large chalk drawings on blackboards made in situ. In the same year he represented Britain at the Venice Biennale, then subsequently won the John Moores Painting Prize (1976), and was nominated for the coveted Turner Prize (1985). The exhibition reveals an artist at the height of his powers, featuring anti-scenic paintings inspired by the coastal landscapes of Maine (United States) where Walker now lives. The freedom with which he is working, and the edgy beauty he achieves as a result, give rise to a refreshing artistic experience of colour and graphic rhythms. Walker's preoccupation with the natural world, and his place in it, is engaging in its essentialism capturing light, space and tidal movement. He is turning paint into land, sea and sky on a coastline that beats to the sound of the Atlantic Ocean, a far cry from the industrial city where he was born and brought up. The artist left Birmingham more than 50 years ago to explore new landscapes, literally and artistically, yet this exhibition represents his long-awaited homecoming. Exhibition: Ikon Gallery, Birmingham, UK (04.12.2019-23.02.2020)
Published to accompany an exhibition held at Ikon Gallery, Birmingham 4 December 2019 - 23 February 2020.
Keywords: Walker, John -- 1939-; Walker, John / 1939- / Exhibitions; Painting, Abstract / Exhibitions; Walker, John / 1939-; Exhibition catalogs; Ausstellungskatalog -- Ikon Gallery -- 04.12.2019-23.02.2020 -- Birmingham; Bildband